2015
DOI: 10.1080/02564602.2015.1068137
|View full text |Cite
|
Sign up to set email alerts
|

Family of Nyquist-I Pulses to Enhance Orthogonal Frequency Division Multiplexing System Performance

Abstract: Artículo de publicación ISISin acceso a texto completoA family of Nyquist-I pulses called sinc parametric linear combination pulse (SPLCP) is proposed. It is characterized by two novel design parameters that provide additional degrees of freedom to minimize the intercarrier interference (ICI) power due to frequency offset. Moreover, it reduces the high peak-to-average power ratio (PAPR) value in orthogonal frequency division multiplexing (OFDM) systems. Several Nyquist-I pulses were recently proposed to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Althloothi et al [26] extracted two sets of 3D spatiotemporal features via a Kinect sensor for human activity recognition, where the shape features were from the surface points using spherical harmonics coefficients, and the motion features were from the end points of the distal limb segments. Besides, similar research work in the area can be found in references [27][28][29].…”
Section: Introductionmentioning
confidence: 85%
“…Althloothi et al [26] extracted two sets of 3D spatiotemporal features via a Kinect sensor for human activity recognition, where the shape features were from the surface points using spherical harmonics coefficients, and the motion features were from the end points of the distal limb segments. Besides, similar research work in the area can be found in references [27][28][29].…”
Section: Introductionmentioning
confidence: 85%
“…As previously explained, a coding matrix has been described that satisfies the orthogonality condition in (52) and that is based on fast WH transforms, so the additional complexity becomes very low. The main reason for spreading symbols over several time slots, as discussed in Section III, is to enable MIMO transmissions in FBMC with approximately the same MIMO complexity as in OFDM.…”
Section: ) Walsh-hadamard Spreading In Timementioning
confidence: 99%
“…The efficiency of IPLCP was analysed in multiplexing schemes based on OFDM in [50], [51]. Additionally, the sinc parametric linear combination pulse (SPLCP) was proposed in [52] and the PMSP was proposed in [53] which attempts to reduce the amplitude of the sidelobes and leads to much better BER performance than ISP. Many pulse shaping filters, such as the exponential linear pulse, were proposed in [54], [55] to decrease the ISI impact in the OFDM scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recognition and segmentation work has involved hybrid methods, such as object recognition, human tracking, activity recognition, and human gait [28][29][30]. Meanwhile, [30] used depth image for face recognition, [26] adopted a similar technique but applied to time attendance systems, and [31] proposed high multiplexing system performance to support face recognition over Wi-Fi. Action recognition, proposed by [32][33][34][35], is more complicated and can be solved using an RGB-D camera with intrinsic features.…”
Section: Introductionmentioning
confidence: 99%